Seeing the world through GREEN‐tinted glasses: Green consumption values and responses to environmentally friendly products - Haws, Kelly L.; Winterich, Karen Page; Naylor, Rebecca Walker (Journal of Consumer Psychology, 2014)
AbstractThe primary goal of this research is to conceptualize and develop a scale of green consumption values, which we define as the tendency to express the value of environmental protection through one's purchases and consumption behaviors. Across six studies, we demonstrate that the six‐item measure we develop (i.e., the GREEN scale) can be used to capture green consumption values in a reliable, valid, and parsimonious manner. We further theorize and empirically demonstrate that green consumption values are part of a larger nomological network associated with conservation of not just environmental resources but also personal financial and physical resources. Finally, we demonstrate that the GREEN scale predicts consumer preference for environmentally friendly products. In doing so, we demonstrate that stronger green consumption values increase preference for environmentally friendly products through more favorable evaluations of the non‐environmental attributes of these products. These results have important implications for consumer responses to the growing number of environmentally friendly products.